Effects of Hemin on Heme Oxygenase-1, Gastric Emptying, and Symptoms in Diabetic Gastroparesis - Bharucha, Adil E. (Neurogastroenterol Motil, 2016)
BACKGROUND: Therapeutic options for management of diabetic gastroparesis are limited. Failure to maintain upregulation of heme oxygenase (HO1) leads to loss of interstitial cells of Cajal and delayed gastric emptying in non-obese diabetic (NOD) mice. Our hypothesis was that hemin upregulation of HO1 would restore normal gastric emptying in humans with gastroparesis. AIMS: To compare effects of hemin and placebo infusions on HO1 activity and protein, gastric emptying, autonomic function, and gastrointestinal symptoms in diabetic gastroparesis. METHODS: In a single-center, double-blind, placebo-controlled, randomized clinical trial, we compared intravenous hemin, prepared in albumin, or albumin alone (placebo) in 20 patients, aged 41±5 (SEM) years with diabetic gastroparesis. After infusions on days 1, 3, and 7, weekly infusions were administered for 7 additional weeks. Assessments included blood tests for HO1 protein and enzyme activity levels, gastric emptying with (13)C-spirulina breath test, autonomic functions (baseline and end), and gastrointestinal symptoms every 2 weeks. RESULTS: Nine of 11 patients randomized to hemin completed all study procedures. Compared to placebo, hemin increased HO1 protein on days 3 (P=.0002) and 7 (P=.008) and HO1 activity on day 3 (P=.0003) but not after. Gastric emptying, autonomic functions, and symptoms did not differ significantly in the hemin group relative to placebo. CONCLUSIONS: Hemin failed to sustain increased HO1 levels beyond a week and did not improve gastric emptying or symptoms in diabetic gastroparesis. Further studies are necessary to ascertain whether more frequent hemin infusions or other drugs would have a more sustained effect on HO1 and improve gastric emptying.